A Rapid Systematic Review of Worldwide Alcohol Use Disorders and Brief Alcohol Interventions in the Criminal Justice System - Newbury-Birch, Dorothy; Ferguson, Jennifer; Connor, Natalie; Divers, Andrew; Waller, Gillian (Frontiers in Psychiatry, 2022)
Although the relationship is complex, there is an association between alcohol use and offending behaviour with an interplay between the amount drank, the pattern of drinking and individual and contextual factors. Alcohol brief interventions have been shown to be effective in primary healthcare, however there is currently a lack of compelling evidence in the criminal justice system. We carried out a rapid systematic review of the literature, which updated our review conducted in 2016. Following systematic searches, we included 36 papers on prevalence and 13 papers on effectiveness. Between 26 and 88% of individuals in the policy custody setting scored positive for an alcohol use disorder. In the magistrates court this was 95%; 31-86% in the probation setting and between 19 and 86% in the prison system. In relation to probable dependence, between 21 and 38% of individuals were shown to have probable alcohol dependence in the police custody suite setting; 39 per cent in the magistrate court system; 17-36% in the probation setting and between 18 and 48% in the prison system. This compares to 6% in the general population. We included 13 studies of effectiveness with differing outcome measures and outcomes. We conclude more studies are needed in the field to develop the current evidence base.